The news frames in the electoral campaigns of 2015 and 2016 in Spain - Melero López, Inmaculada (Historia y Comunicación Social, 2023)
This study deals with an approach to the media coverage used in the electoral campaign and the predominance of some frames over others in their agenda. To analyze the framings of the media, a content analysis of the newspapers El País, El Mundo and ABC is carried out during the 2015 and 2016 campaigns. The analysis is carried out based on four essential framings: strategic, subject, of conflict and debate and political agreement. As usual in the electoral campaign period, a notorious presence of the strategic framework is observed, appealing to tactics and mechanisms of competition between leaders in a context of change in the party system in Spain. The presence of the rest of the frames is also modified in both campaigns according to factors that intervene in the political cycle.